Barriers Faced by Deaf Individuals while Availing Speech and Hearing Services - Reuben Thomas Varghese; Rajkumar Rimmalapudi; Rubby Viren; Karthik Venkat Sridaran; Reshma Odungattu; Govindaraju Teja (Auditory and Vestibular Research)
Background and Aim: Deaf individuals in India face significant auditory impairment, leading to challenges in accessing services. Studies highlight the need to enhance communication services and accessibility to ensure fair access to resources for the deaf community. The present study aimed to address the barriers faced by deaf individuals while availing speech and hearing services in India. Methods: A total of 325 deaf individuals were considered in the age range of 18–30 years, and a survey research design was employed. A 25-item questionnaire was developed under three domains: communication barriers, service access barriers, and psychological barriers. The questionnaires were given to the participants to fill, and the responses were calculated. Results: The overall results revealed that service access barriers were more compared to communication barriers and psychological barriers. In services-related barriers, the results revealed communication barriers, 74% of the participants preferred sign language during speech and hearing consultations and required counselling by professionals in sign language. Further, in terms of psychological barriers, 70% of participants lacked confidence in visiting speech and hearing institutes/clinics. Moreover, 78.8% of participants reported a need for more materials in sign language at the appointment sections and a lack of sign language interpreters while accessing services in terms of service access barriers. Conclusion: Addressing these barriers faced by deaf individuals is critical to ensure equitable access to services and promote positive experiences while they are availing speech and hearing services.